ANALYSIS OF EFFECTIVENESS, EFFICIENCY OF MOTOR VEHICLE TAX AND CUSTOMS OF MOTOR VEHICLES IN THE NAME BEHIND THE EFFORT TO INCREASE REVENUE REGIONAL ORIGINAL (A Case Study BPKD D. I. Yogyakarta Province - Ria, Gustin Fajar; Legowo.,M.Si.,Akt, Drs. H.Herman (Accounting, 2009)
Based on Law No. 5 of 1974 on the main points of governance in the region result in stacking strength and power in certain groups and poverty in these areas. Because of applying centralized governance and finance, it dikemungkinkan happen because of potential revenue sources in the area is almost entirely drawn kepemerintah center with a pattern for a very adverse outcome In the framework of decentralization, local governments need funding and financing to implement regional development. One source of funds for development financing used by the local government is a government savings is the difference between local revenues and expenditures. PAD is an important source of local revenue in an effort to increase local autonomy In line with the reform of governance, then the system of governance in the region was changed so that birth Law. 22, 1999 which has been converted into Law no. 32 of 2004 on the implementation of regional autonomy, where government authority is the responsibility of their own regions, with regional autonomy was given greater authority to regulate and manage their own household. In line with the authority of local government are expected to explore the sources of finance, particularly to meet the financing needs of government and local development through local revenue (PAD). One type of local taxes which are a major revenue is from vehicle tax and customs behind the name of motor vehicles. The size of revenue reflects the ability of an area to organize and manage their households, especially in order to explore the sources oflocal finance in terms of cost and within the framework of the implementation of regional development are real and responsible. Keywords : effectiviness,efficiency of motor vehicles tax